Electrochemical Synthesis of TiO2 under Pulse Alternating Current: Effect of Thermal Treatment on the Photocatalytic Activity. Issue 6 (11th February 2019) - Ulyankina, Anna; Avramenko, Marina; Kusnetsov, Denis; Firestein, Konstantin; Zhigunov, Denis; Smirnova, Nina
Abstract: The current work aimed to study the effect of thermal treatment on the structural, optical, and photocatalytic properties of TiO2 nanoparticles synthesized by a novel large‐scale electrochemical method using pulse alternating current (PAC). The obtained titania was characterized via XRD, TEM, XPS, UV‐Vis DRS, PL, Raman and FTIR spectroscopy. The as‐prepared TiO2 was found to be poorly crystallized and partly amorphous. Following thermal annealing, the anatase structure is developed at temperatures of 400–600 °C. The photoreactivity of the TiO2 nanoparticles was evaluated for the degradation of methylene blue (MB) and rhodamin B (RhB) dyes under UVA irradiation. As shown, the adsorption properties and photocatalytic activity of the as‐prepared TiO2 strongly depend on the chemical nature of the dye. The enhanced photocatalytic performance for the MB and RhB degradation was observed for the sample annealed at 400 °C, which coincides with a balance between the degree of crystallinity, specific surface area, optical properties and efficiency of electron‐hole pair separation. Abstract : TiO2 ‐NPs were successfully prepared via a large‐scale and environmentally friendly electrochemical method using pulse alternating current (PAC synthesis). The effect of thermal treatment on the structural, optical, and photocatalytic properties of TiO2 ‐NPs was investigated. The results demonstrated that the adsorption/photocatalytic properties of the poorly crystalline TiO2 strongly depended on the chemical nature of the dye. The photoactivity of anatase TiO2 for MB and RhB degradation decreased with increase in annealing temperature from 400 °C to 600 °C.